Diliman Student Center a feasibility study - Aspiras, Aira; Cano, Gellie Anne Mae; Felipe, Dianne Joy (Quezon City College of Engineering, University of the Philippines Diliman, 2010)
The Diliman Student Center is facility that aims to provide attending and legitimate students of the University of the Philippines, Diliman a safe student-friendly place where they can work on individual and group projects until late at night. It will be located on the North Wing section of the Main Library, Gonzales Hall. Operating hours will be from 5PM-9AM. The layout of the facility includes individual and group discussion rooms. Other services such as free wi-fi, printing and photocopying will also be offered in the facility. There will be vending machine, ATM, supplies stores and others that will make the facility a comfortable and convenient place for students to work in. With the trend in changing lifestyles and study habits of students, the need for such facility is determined and how the idea would sell to the chosen market is found. What the cusomers want in the facility became the basis of the marketing schemes and specifications such as the services provided and the layout. The financial aspects of putting up such facility are also included in this study. Investment costs, operating and maintenance costs and expected revenue are computed. The financial evaluation is done for five years. Social and Economics profitability of the Diliman Student Center is of great importance to this study. It establishes the importance of facility not only for the sudents but also for the university. In conclusion, this study proves that the Diliman Student Center is market, technically, financially, socially and economically feasible.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Student unions -- Design and construction; University of the Philippines -- Buildings; Feasibility studies